Peran dan Urgensi Psikologi Pembelajaran Pendidikan Agama Islam - Musdalifah Nihaya (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
One of the materials contained in Islamic religious education books is a discussion of fasting. Fasting is the main worship which is defined as one of the pillars of Islam that must be done for a Muslim. Basically, fasting in the understanding of students tends to be limited by the terms and harmony in the learning process, while the nature of fasting in the form of appreciation and practice of the values of spirituality and morality gets less attention. So the purpose of this study is to determine the urgency of the development of Islamic Religious Education learning in teaching material "fasting" in the perspective of psychology on the motivation of student worship. This research uses library research method, which is looking for theoretical references that are relevant to the problems found. The results of this study indicate that fasting if carried out sincerely has enormous benefits for the psychology of human life. Among them, fasting is beneficial for mental health, mental calmness, social values, and as an exercise in self-control (Self Control), so that in itself embedded positive qualities from the influence of the implementation of fasting. Therefore, the importance of psychology in developing Islamic religious education learning in fasting teaching materials is to foster student motivation in fasting so as to increase students' love for the implementation of fasting.